Improving the Performance of Hybrid RoF-FSO Optical Communication Systems Using an Adaptive Optical Receiver (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Engineering Sciences Series, 2026)
All modern broadband services rely on optical fibers as a fundamental infrastructure, including mobile and satellite networks that benefit from integrating RoF signal transmission with FSO technology. This hybrid architecture faces key challenges arising from electronic thermal noise and atmospheric attenuation, which limit the range and efficiency of communication links. This research aims to address these challenges by proposing an adaptive optical receiver tailored for hybrid RoF-FSO communication systems. The proposed receiver operates by instantaneously estimating the signal-to-thermal noise ratio and injecting a dynamic compensation current that elevates the signal level above the detection threshold prior to the decision stage. A mathematical model of the proposed circuit was developed and evaluated using MATLAB simulations within a hybrid network employing WDM-PDM with a total capacity of 160 Gbps. Results demonstrate the proposed solution's effectiveness, achieving a transmission range of 26.5 km (96.3% improvement) under clear weather conditions, and 21 km (82.6% improvement) under hazy conditions, alongside enhancements ranging between 40% and 46% under other examined atmospheric scenarios.
Keywords: Hybrid RoF-FSO System, Adaptive Optical Receiver, WDM-PDM, Atmospheric Attenuation.